Treinamento auditivo: avaliação do benefício em idosos usuários de próteses auditivas - Megale, Renata Luciane (2010)
BACKGROUND: hearing impairment has a negative impact on communication. This impact can be minimized by hearing aids fitting and auditory training. AIM: to verify the effectiveness of auditory training in elderly individuals, new users of hearing aids, regarding the benefit in fitting. METHOD: forty-two individuals with mild to moderate neurosensorial hearing loss, ranging in age from 60 to 90 years, were selected. Individuals were new users of bilateral hearing aids and were divided in two groups: Experimental Group (EG) and Sham Group (SG). The EG was submitted to training in an acoustic cabin during six sessions. Both groups were assessed through the following tests: Speech in Noise, Dichotic Digits and the Abbreviated Profile of Hearing Aid Benefit Aphab self-assessment questionnaire, without the hearing aids, four and eight weeks after they were fitted. RESULTS: there was a statistically significant difference between the groups in both of the used tests, and for the Abbreviated Profile of Hearing Aid Benefit Aphab in the second and third assessments in the sub-scales of: Communication Easiness, Reverberation and Environmental Noise. CONCLUSION: auditory training favored the improvement in the auditory processing abilities and benefited the hearing aid fitting process.